Phylogenomics With Hyb-Seq Unravels Korean Hosta Evolution - Yoo, Mi-Jeong; Lee, Byoung-Yoon; Kim, Sangtae; Lim, Chae Eun (Frontiers in Plant Science, 2021)
The genus Hosta (Agavoideae and Asparagaceae) is one of the most popular landscaping and ornamental plants native to temperate East Asia. Their popularity has led to extensive hybridization to develop various cultivars. However, their long history of hybridization, cultivation, and selection has brought about taxonomic confusion in the Hosta species delimitation along with their indistinguishable morphology. Here, we conducted the first broad phylogenetic analyses of Hosta species based on the most comprehensive genomic data set to date. To do so, we captured 246 nuclear gene sequences and plastomes from 55 accessions of Korean Hosta species using the Hyb-Seq method. As a result, this study provides the following novel and significant findings: (1) phylogenetic analyses of the captured sequences retrieved six species of Hosta in South Korea compared to five to eleven species based on the previous studies, (2) their phylogenetic relationships suggested that the large genome size was ancestral and the diversification of Korean Hosta species was accompanied by decreases in genome sizes, (3) comparison between nuclear genes and plastome revealed several introgressive hybridization events between Hosta species, and (4) divergence times estimated here showed that Hosta diverged 35.59 million years ago, while Korean Hosta species rapidly diversified during the late Miocene. Last, we explored whether these genomic data could be used to infer the origin of cultivars. In summary, this study provides the most comprehensive genomic resources to be used in phylogenetic, population, and conservation studies of Hosta, as well as for unraveling the origin of many cultivars.